Synergistic Undernutrition: The Metabolic Nexus Between Chronic Energy Deficiency and Anemia in Rural Balinese Pregnant Women - I Putu Adigama; I Nyoman Sayang; Gusti Ngurah Nyoman Yuliastina; I Made Pasek Soma Gauthama (HM Publisher, 2025)
Despite the widespread implementation of Iron-Folic Acid (IFA) supplementation programs, the prevalence of maternal anemia in Indonesia remains stagnant, suggesting a multifactorial etiology beyond simple micronutrient deficiency. In rural agrarian settings, macronutrient adequacy—specifically protein-energy balance—may play a critical, yet overlooked, role in hematopoiesis. This study investigates the